2019
DOI: 10.1021/acs.chemmater.9b03709
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Availability of Bromide Dictates CsPbBr3 Nanocrystal Growth

Abstract: Lack of detailed understanding of the growth mechanism of CsPbBr 3 nanocrystals has hindered sophisticated morphological and chemical control of this important emerging optoelectronic material. Here, we have elucidated the growth mechanism by slowing the reaction kinetics. When 1bromohexane is used as an alternative halide source, bromide is slowly released into the reaction mixture, extending the reaction time from ∼3 s to greater than 20 min. This enables us to monitor the phase evolution of products over th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…In addition, different Cs + or Pb 2+ sources react to form CsPbBr 3 PQDs at different rates. [ 32 ] Figure S1b,c in the Supporting Information shows the PL spectra of composites with different Cs + or Pb 2+ sources. As seen in both figures, the use of CH 3 (CH 2 ) 16 COOCs, [CH 3 (CH 2 ) 16 COO] 2 Pb, and KBr in the 1:1:3 molar ratio (hereafter abbreviated as CCK) as the raw materials of the perovskites results in the strongest emission of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, different Cs + or Pb 2+ sources react to form CsPbBr 3 PQDs at different rates. [ 32 ] Figure S1b,c in the Supporting Information shows the PL spectra of composites with different Cs + or Pb 2+ sources. As seen in both figures, the use of CH 3 (CH 2 ) 16 COOCs, [CH 3 (CH 2 ) 16 COO] 2 Pb, and KBr in the 1:1:3 molar ratio (hereafter abbreviated as CCK) as the raw materials of the perovskites results in the strongest emission of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike cationic components, there are few reports on anionic component (halide) induced phase change of Cs–Pb–X which also helped to tune the phase and morphology of the perovskite nanocrystals. A Br-deficient environment might also lead to the formation of CsPbBr 3 through CsBr and Cs 4 PbBr 6 intermediates, suggesting that bromine might also induce transformation from Cs 4 PbBr 6 to CsPbBr 3 …”
mentioning
confidence: 99%
“…A Br-deficient environment might also lead to the formation of CsPbBr 3 through CsBr and Cs 4 PbBr 6 intermediates, suggesting that bromine might also induce transformation from Cs 4 PbBr 6 to CsPbBr 3 . 54 Moreover, fast nucleation of ionic halide perovskites and the competition between coordinated solvent molecules or ligands and halide ions to form distorted octahedrons with Pb(II) ions in solution ion equilibrium resulted in the formation of V Br − defects, as shown in Figure 6a. 55 Hence, more halide ions in octahedrons during nucleation led to fewer V Br − defects, resulting in higher PLQY in several cases.…”
mentioning
confidence: 99%
“…However, upon washing this is not observable. The transition between these two phases is extremely facile for this phase, particularly for the sample synthesized at 100 C. Wen et al 31 showed a phase evolution occurring within a short period of 2 hours. Further repeated measurements of this sample show varying intensity ratios for the two phases suggesting the role of the environment in an extremely long measurement timescale ($4 hours).…”
Section: Resultsmentioning
confidence: 99%